Model to Evaluate the Performance of Building Integrated Photovoltaic Systems using Matlab/Simulink - Julian Andres Camacho Castro; Andres Julian Aristizabal Cardona (International Journal of Electrical and Computer Engineering (IJECE), 2018)
This article describes a mathematical model implemented in Matlab/Simulink to evaluate the performance of building integrated photovoltaic systems (BIPVS). The proposed methodology allows to model independently the solar panel, the photovoltaic (pv) generator, inverter and the grid to integrate them into a single model in Simulink in order to evaluate the performance of the complete system. The validation of the model was made on a BIPV system of 6 kWp installed in a building at the Universidad de Bogotá Jorge Tadeo Lozano in Bogota, Colombia. The results indicate that there is a correlation greater than 0.9 between DC and AC power generated by the BIPV system and calculated by the model proposed for any weather condition.